Localisation of Bladder Incontinence Based on History and Examination for First-Year Neurosurgical Residents - Shareef, Ismail Junaih; Abdullah, Jafri Malin; Zakaria, Zaitun; Yop, Wing Hang; Zainol, Mohamad Haikal; Suliman, Fadhli; Bahri, Azwa Maulat Kamarul; Wen, Aaron Lee Zhi; Jap, Xin Yi; Zulkifli, Muhammad Zakwan; Shukri Soo, Muhammad Afifi (Malaysian Journal of Medical Sciences, 2026)
When a patient presents with urinary incontinence, the goal is to quickly localise the cause of it, so that further imaging workup and targeted management can be initiated at the earliest. In this review, we look at established functional magnetic resonance imaging data and activation likelihood estimation analysis to pinpoint specific areas of the nervous system causing urinary incontinence. These can range from the cortex and the pontine micturition centre to the spinal pathway and peripheral nerves. By using basic history-taking and examination techniques, the five main types of urinary incontinence can be localised to specific anatomical locations.